ANALISIS PENGARUH PELAYANAN PENDAFTARAN TANAH TERHADAP KEPUASAN MASYARAKAT PADA KANTOR PERTANAHAN KOTA LANGSA - Nafisah, Siti Rafa'; Nurviana; Fairus; Saiman (JURNAL GAMMA-PI, 2022)
The purpose of this study was to determine the quality of community satisfaction with the services of the Langsa City Land Office and also to determine the analysis of the effect of land registration services on the satisfaction of the people of Langsa City. The data used is primary data in the form of questionnaires distributed to 30 respondents. The data is sourced from the people of Langsa City. The data from the questionnaire were analyzed by simple regression. Based on the analysis, it was found that the level of community satisfaction with the Langsa City Land Office was quite good with the results of the Respondes Achievement Level above 75%, the percentage value of the influence of community satisfaction on land registration information was 14.2%.